The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.nmni.2020.100669
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and intracerebral haemorrhage: causative or coincidental?

Abstract: Pneumonia appears to be the most common manifestation of coronavirus disease 2019 (COVID-19), but some extrapulmonary involvement, such as gastrointestinal, cardiac and renal, has been reported. The limited clinical data about the virus's behavior to date, especially extrapulmonary symptoms, suggest that we should be aware of the possibility of initial cerebrovascular manifestations of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
293
2
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(320 citation statements)
references
References 6 publications
9
293
2
9
Order By: Relevance
“…Activation of the coagulation cascade leading to disseminated intravascular coagulation can signi cantly contribute to the multiorgan involvement in patients with COVID-19, resulting in acute ischemic stroke, cerebral venous sinus thrombosis or intracerebral hemorrhage [8,40,41]. Moreover, the adhesion of SARS-CoV-2 to ACE2 receptors gains particular importance in the cases of intracerebral hemorrhage due to the inactivation of the receptor and subsequent dysfunction in blood pressure regulation [8,11,15,20,40]. It is also possible that some cases of ischemic stroke in COVID-19 patients have a cardio-embolic source from virus-related cardiac injury [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the coagulation cascade leading to disseminated intravascular coagulation can signi cantly contribute to the multiorgan involvement in patients with COVID-19, resulting in acute ischemic stroke, cerebral venous sinus thrombosis or intracerebral hemorrhage [8,40,41]. Moreover, the adhesion of SARS-CoV-2 to ACE2 receptors gains particular importance in the cases of intracerebral hemorrhage due to the inactivation of the receptor and subsequent dysfunction in blood pressure regulation [8,11,15,20,40]. It is also possible that some cases of ischemic stroke in COVID-19 patients have a cardio-embolic source from virus-related cardiac injury [11].…”
Section: Discussionmentioning
confidence: 99%
“…2). Thirty-one patients experienced a cerebrovascular complication, with 27 ischemic strokes [11,[19][20][21][22][23], 3 hemorrhagic strokes [11,15,23] and 1 cerebral venous sinus thrombosis [11]. There were 15 patients with GBS [13,14,[24][25][26][27][28][29][30] or its variants, 6 reported as encephalitis [12,18,[31][32][33], one with seizures [34], one with acute hemorrhagic necrotizing encephalopathy [16] one reported as transverse myelitis [35], and one reported as ADEM [36].…”
mentioning
confidence: 99%
“…ACE2 is a multispecific enzyme. Although ACE2, located in the surface of lung alveolar epithelial cells among others (Hamming et al 2004;Zou et al 2020) is a receptor for SARS coronaviruses including SARS-CoV-2 (Yan et al 2020;Shang et al 2020), it is also a demonstrated protective factor for SARS in the lung (Jia 2016). ACE2 cleaves Angiotensin II into Ang (1-7), part of the ACE2/Angiotensin (1-7)/Mas axis, a proposed protective mechanism balancing RAS overstimulation, and this system is stimulated by ARBs (Ren et al 2019).…”
Section: Ace2 As a Therapeutic Target In Fighting Sars-cov-2 Infectionmentioning
confidence: 99%
“…(9) By now, three cases have been reported with massive intracerebral hemorrhage. (10,11) During the treatment of our cohort of critical ill COVID-19 patients, three fatal intracerebral hemorrhages occurred. We therefore raised the question if intracerebral hemorrhage is more common in critically ill COVID-19 patients with respiratory failure compared to the general population of patients with acute respiratory distress syndrome (ARDS).…”
Section: Introductionmentioning
confidence: 96%